2018
DOI: 10.5603/gp.a2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of experimental diabetes and chronic hypoxia on rat fetal body weight

Abstract: Objectives: The aim of the study is to determine the impact of the experimental diabetes and the chronic hypoxia on pregnancy development and rat fetal body weight. Material and methods:The experiment was performed on female Wistar rats. Animals were divided into the experimental groups. I -Controls, II -Untreated diabetes, III -Insulin-treated diabetes, IV -No diabetes with chronic hypoxia, V -Untreated diabetes and chronic hypoxia, VI -Insulin-treated diabetes and chronic hypoxia. Diabetes was induced in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The DV group, in addition to developing severe hyperglycemia maintained during the experiment, presented fewer implantations and embryos, as well as an increase in preimplantation losses, which are characteristic of the model used, widely used in diabetes and pregnancy studies 22,23,26,32 . In this model it is shown that the alterations of reproduction depend on maternal hyperglycemia and not on streptozotocin; this substance is eliminated from circulation a few hours after its administration 31 , so it does not affect reproduction when administered before gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DV group, in addition to developing severe hyperglycemia maintained during the experiment, presented fewer implantations and embryos, as well as an increase in preimplantation losses, which are characteristic of the model used, widely used in diabetes and pregnancy studies 22,23,26,32 . In this model it is shown that the alterations of reproduction depend on maternal hyperglycemia and not on streptozotocin; this substance is eliminated from circulation a few hours after its administration 31 , so it does not affect reproduction when administered before gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The research was developed in the Department of Biochemistry of the Institute of Basic and Preclinical Sciences "Victoria de Girón", in the period from 2019 to 2021. In each group, a number of animals similar to the smallest number used in previous experimental studies of diabetes and pregnancy in rats was used 22,23 . The project was approved by the Scienti c Council and the Research Ethics Committee of the institution.…”
Section: Methodsmentioning
confidence: 99%